A corrosion-protective coating based on a solution-processable polymer-grafted graphene oxide nanocomposite. (September 2015) - Qi, Kai; Sun, Yimin; Duan, Hongwei; Guo, Xingpeng
Highlights: Solution-processable polymer-grafted graphene nanocomposite is synthesized. The nanocomposite exhibits synergistic properties of both building blocks. The nanocomposite can be easily applied to form a protective coating on metals. The coating can effectively prevent corrosion of copper substrate. Abstract: A new type of solution-processable graphene coating has been synthesized by grafting polymethylmethacrylate (PMMA) brushes on graphene oxide (GO) via surface-initiated atom transfer radical polymerization (ATRP). One major finding is that the PMMA-grafted GO nanocomposite exhibits synergistic properties of both building blocks, i.e., permeation inhibition of GO and solubility of PMMA in a variety of solvents, which makes it compatible with commonly used coating methods to form uniform coatings with controlled thickness. Our results demonstrate that PMMA-grafted GO coating can effectively block charge transfer at the metal–electrolyte interface and prevent corrosion of the copper substrate under aggressive saline conditions.